1997
DOI: 10.1088/0031-9155/42/8/008
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the ferric diffusion coefficient in agarose and gelatine gels by utilization of the evolution of a radiation induced edge as reflected in relaxation rate images

Abstract: A method has been developed to determine the diffusion coefficients of ferric ions in ferrous sulphate doped gels. A radiation induced edge was created in the gel, and two spin-echo sequences were used to acquire a pair of images of the gel at different points of time. For each of these image pairs, a longitudinal relaxation rate image was derived. From profiles through these images, the standard deviations of the Gaussian functions that characterize diffusion were determined. These data provided the basis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 18 publications
1
43
2
1
Order By: Relevance
“…The local water diffusion coefficient (sometimes referred to as the free diffusion coefficient) or the corresponding media viscosity has been inferred from a variety of studies employing small molecules or ions as reporter species. Derived water diffusion coefficient values ranging from 1 · 10 À5 cm 2 /s in cells to 1 · 10 À6 cm 2 /s in 4% agarose gels [24][25][26][27][28] are typical. In the laboratory frame, R OS 1 has a maximum and appears at frequency $20 MHz only if the diffusion coefficient is sufficiently low, i.e., D < 5 · 10 À6 cm 2 /s.…”
Section: Inner Shell Water Contributionmentioning
confidence: 99%
“…The local water diffusion coefficient (sometimes referred to as the free diffusion coefficient) or the corresponding media viscosity has been inferred from a variety of studies employing small molecules or ions as reporter species. Derived water diffusion coefficient values ranging from 1 · 10 À5 cm 2 /s in cells to 1 · 10 À6 cm 2 /s in 4% agarose gels [24][25][26][27][28] are typical. In the laboratory frame, R OS 1 has a maximum and appears at frequency $20 MHz only if the diffusion coefficient is sufficiently low, i.e., D < 5 · 10 À6 cm 2 /s.…”
Section: Inner Shell Water Contributionmentioning
confidence: 99%
“…Diffusivity through biopolymers is critical in many biomedical and biochemical applications such as bioreactor systems using immobilized cells and enzymes (Merchant et al, 1987;Blanch and Clark, 1996;Pilkington et al 1998), drug delivery systems (Wood and Calton, 1993;Peppas and Wright, 1996), radiation dosimetric gels (Rae et al, 1996;Kron et al, 1997;Pedersen et al, 1997), and pancreatic islet encapsulation (Watler et al, 1988;Kessler et al, 1992). Traditional chemical engineering methods used for measuring the diffusion coefficient of a solute through a polymer sample requires an analytical technique (Geankoplis, 1978;Willard et al, 1981) to determine the solute concentration (within or adjacent to the sample) as a function of time.…”
Section: Diffusionmentioning
confidence: 99%
“…Skretting et al, Oslo, reported on how the diffusion coefficient can be determined by image processing of MRIs of the evolution of a radiation-induced edge in a gel phantom. They have also shown that the diffusion coefficient can be lowered by almost a factor of 2 by adding xylenol orange to the gel solution (19).…”
Section: Dosimetrymentioning
confidence: 99%